Als3‐Th‐cell‐epitopes plus the novel combined adjuvants of CpG, MDP, and FIA synergistically enhanced the immune response of recombinant TRAP derived from Staphylococcus aureus in mice. Issue 3 (19th May 2021) - Ma, Jinzhu; Liu, Wei; Wang, Beiyan; Yu, Simiao; Yu, Liquan; Song, Baifen; Yu, Yongzhong; Zhu, Zhanbo; Cui, Yudong
Abstract: Introduction: Staphylococcus aureus ( S. aureus ) is a gram‐positive opportunistic pathogen, there are currently no high effective vaccine against S. aureus in humans and animals, the development of an efficient vaccine remains an important challenge to prevent S. aureus infection. Here, we prepared Als3‐Th‐cell‐epitope‐Target of RNAIII Activating Protein (TRAP) (ATT) proteins plus the novel combined adjuvants to develop a promising vaccine candidate against S. aureus . Methods: The recombinant pET‐28a (+)‐ att plasmids were constructed, and the ATT proteins were expressed and obtained, then, ATT plus Freund's adjuvant or the novel combined adjuvants of cytosine‐phosphate‐guanosine oligodeoxynucleotides (CpG), muramyl dipeptides (MDP), and FIA were immunized in mice. After booster immunization, the levels of interferon‐γ (IFN‐γ), interleukin‐4 (IL‐4), IL‐10 and IL‐17A cytokine were evaluated, the humoral immune responses against TRAP were detected in mice, and the survival rate of mice was confirmed by challenge assay. Results: The mice immunized with ATT plus Freund's adjuvant exhibited significantly higher level of IFN‐γ, IL‐4, IL‐10, and IL‐17A, and displayed the stronger humoral immune response against TRAP than control groups, importantly, the survival rate of these mice was significantly higher than control groups. In addition, compared with the control groups, ATT + CpG + MDP + FIA group was elicited significantly higher level of IFN‐γ, IL‐4, IL‐10, and IL‐17A and was triggered the stronger humoral immune responses against TRAP, moreover, generated the higher survival rate of mice. Conclusion: Als3 epitopes significantly enhanced TRAP immunogenicity. ATT plus the novel combined adjuvants of CpG, MDP, and FIA induced the strong immune response and protection against S. aureus, revealing the combination of CpG, MDP, and FIA adjuvant acts the synergistic effect. Abstract : The recombinant ATT proteins were expressed and prepared. ATT plus the novel combined adjuvants of MDP, CpG, and FIA induced the strong immune response and protection against S. aureus in mice, revealing the novel combined adjuvant acts the synergistic effect.